Organizational Culture, Leadership and Sustainable Economic Growth in the Age of Artificial Intelligence - Suwestian, M Firdaus (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Technological developments and the increasingly advanced digital era have brought significant changes in the business and economic world. Adoption of artificial intelligence (AI) is considered as one of the solutions to encourage sustainable economic growth in this era. However, the implementation of AI in organizations also influences organizational culture and leadership, thus requiring deeper studies regarding the relationship between organizational culture, leadership, and sustainable economic growth in the AI ​​era. This article aims to explore the relationship between these three aspects, as well as provide recommendations for organizations in managing their culture and leadership to achieve sustainable economic growth in the AI ​​era. This study uses qualitative methods by collecting data through interviews with leaders and members of the organization. The research results show that strong organizational culture and leadership can influence sustainable economic growth in the AI ​​era, and there needs to be an appropriate strategy in managing culture and leadership to achieve this goal. Managerial implications and recommendations for organizational practitioners are also discussed in this article.